Large Scale Synthesis of Carbon Nanofibres on Sodium Chloride Support - Ravindra Rajarao; Badekai Ramachandra Bhat (Nanomaterials and Nanotechnology)
Large scale synthesis of carbon nanofibres (CNFs) on a sodium chloride support has been achieved. CNFs have been synthesized using metal oxalate (Ni, Co and Fe) as catalyst precursors at 680 C by chemical vapour deposition method. Upon pyrolysis, this catalyst precursors yield catalyst nanoparticles directly. The sodium chloride was used as a catalyst support, it was chosen because of its non‐toxic and water soluble nature. Problems, such as the detrimental effect of CNFs, the detrimental effects on the environment and even cost, have been avoided by using a water soluble support. The structure of products was characterized by scanning electron microscopy, transmission electron microscopy and Raman spectroscopy. The purity of the grown products and purified products were determined by the thermal analysis and X‐ray diffraction method. Here we report the 7600, 7000 and 6500 wt% yield of CNFs synthesized over nickel, cobalt and iron oxalate. The long, curved and worm shaped CNFs were obtained on Ni, Co and Fe catalysts respectively. The lengthy process of calcination and reduction for the preparation of catalysts is avoided in this method. This synthesis route is simple and economical, hence, it can be used for CNF synthesis in industries.